ROS induced lipid peroxidation and their role in ferroptosis - Endale, Hiwot Tezera; Tesfaye, Winta; Mengstie, Tiget Ayelgn (Frontiers in Cell and Developmental Biology, 2023)
Reactive oxygen species (ROS) play a crucial part in the process of cell death, including apoptosis, autophagy, and ferroptosis. ROS involves in the oxidation of lipids and generate 4hydroxynonenal and other compounds associated with it. Ferroptosis may be facilitated by lipid peroxidation of phospholipid bilayers. In order to offer novel ideas and directions for the investigation of disorders connected to these processes, we evaluate the function of ROS in lipid peroxidation which ultimately leads to ferroptosis as well as proposed crosstalk mechanisms between ferroptosis and other types programmed cell death.